Enquête: Kikanago: la résistance amérindienne - Radio-Canada Info (2016)
Kikanago : la résistance amérindienne Cette histoire inédite raconte la résistance de familles amérindiennes qui ont défié l’Église et le gouvernement. Marie-Jeanne, William et Grégoire, devenus adultes, nous disent comment leurs parents les ont protégés des pensionnats où tant d’enfants ont subi des sévices divers. L’histoire se passe à Val-d’Or et sur la Côte-Nord, mais aussi en Saskatchewan. Enquête a pu assister aux retrouvailles, soixante ans plus tard, entre Lyndia et la Famille Goodwin qui l’a protégée des pensionnats autochtones. Journaliste : Josée Dupuis Réalisatrice : Jo-Ann Demers Caméramans: Luc Simard, Luc Delorme, Cory Herperger Preneur de son: Éric Celton Monteuse: Hélène Morin
Keywords: 1900-1999; 1950-1959; 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; féminisme autochtone; histoire et politique; pensionnats; pol5480; premier cycle; périodes historiques; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violences

Decolonizing trauma studies: Trauma and postcolonialism - Andermahr, Sonya (MDPI AG - Multidisciplinary Digital Publishing Institute, 2016)
This Special Issue aims to explore the complex and contested relationship between Trauma Studies and postcolonial theory, focusing on the possibilities for creating a decolonized trauma theory that takes account of the suffering of minority groups and non-Western cultures, broadly defined as cultures beyond Western Europe and North America. The issue builds on the insights of, inter alia, Stef Craps's book, Postcolonial Witnessing, and responds to his challenge to interrogate and move beyond a Eurocentric trauma paradigm.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; discours dominant; décolonialisme; périodes historiques; ressource en ligne; système colonial; systèmes d'oppressions; trauma

Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Women, girls and world poverty: empowerment, equality or essentialism? - Chant, Sylvia (International Development Planning Review, 2016)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; angleterre; approches et analyses; corps; cours; discipline; empowerment; europe; féminisme décolonial; patriarcat; pauvreté; pol4022; premier cycle; périodes historiques; régions géographiques; science politique; système colonial; systèmes d'oppressions; thématiques

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
https://uqam-bib.on.worldcat.org/oclc/953804743
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

La portée réparatrice et réconciliatrice de la Commission de vérité et réconciliation du Canada - Jaccoud, Mylène (Recherches amérindiennes au Québec, 2016)
Cet article examine les potentialités réparatrices et réconciliatrices de la Commission de vérité et réconciliation (CVR) qui a été mise en place au Canada de 2008 à 2015 en réponse aux traumatismes vécus par les autochtones dans les pensionnats. L’auteure conclut que ces potentialités sont relativement limitées. Les principales limites tiennent à l’absence d’un espace de dialogue entre les victimes et les responsables, à une centration sur les narratifs traumatiques des victimes mais aussi à une conception dépolitisée du principe de la réconciliation. La CVR du Canada n’a pas inscrit la décolonisation comme vecteur de réconciliation mais a préféré s’engager dans la voie d’une pacification des relations entre les peuples. Or, l’auteure soutient que la réconciliation entre les peuples autochtones et l’État nécessite de dépasser les gestes de guérison et de réparation matérielle ou symbolique. La décolonisation des institutions, la redistribution des territoires et une réforme constitutionnelle en profondeur restent les seules avenues possibles pour parvenir à réconcilier avec ses oppresseurs un peuple victime d’un génocide culturel.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; capitalisme; commission de vérité et réconciliation; cours; criminologie; discipline; droits des personnes autochtones; féminisme décolonial; histoire et politique; justice réparatrice; justice sociale; peuples autochtones; pol4102; premier cycle; périodes historiques; racisme; réconciliation; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Kaianishkat : pour la création d'un réseau de chercheures communautaires autochtones. Outils de formation à la recherche - Jérôme, Laurent; Léger, Marie; Michel, Viviane; Otteyres, Joanne; Riverin, Josée-Anne (2016)
« Ce site se veut à la fois le récit de Kaianishkat, un projet de formation à la recherche destinée à des femmes autochtones en communauté, et un espace de partage des outils d’accompagnement à la recherche qui ont été codéveloppés tout au long de ce projet, [...] sous forme de courtes fiches explicatives des principaux éléments à considérer dans le cadre de la réalisation d’une recherche. Ces fiches, destinées en premier lieu à des femmes autochtones souhaitant réaliser des projets de recherche en communauté, peuvent, en revanche, être utiles à quiconque veut amorcer un processus de recherche » [Portion du résumé original]
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; autochtones; formations; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; québec; recherche en milieux de pratique; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions

Sexualized Violence and Colonialism: Reflections on the Inquiry into Missing and Murdered Indigenous Women - Razack, Sherene (Canadian Journal of Women and the Law, 2016)
Introduction to the special isuue of the Canadian Journal of Women and the Law on the "Missing and Murdered Indigenous Women Conference".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminicide; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences